Case Report: an extremely rare case of giant dedifferentiated retroperitoneal liposarcoma - Chua, Huey Bing; Hussain, Rizuana Iqbal; Shukor, Nordashima Abd; Fam, Xeng Inn (Frontiers in Oncology, 2025)
Retroperitoneal liposarcoma, especially dedifferentiated liposarcoma (DDL), is a rare tumor type primarily affecting middle-aged and older adults in the retroperitoneum or proximal extremities. This case report highlights an exceptionally large retroperitoneal DDL that had enveloped the entire right kidney and had adhered to nearby tissues. Diagnosing retroperitoneal liposarcoma is challenging due to its asymptomatic nature until it reaches a substantial size. Imaging, particularly contrast-enhanced computed tomography (CECT), play a vital role in diagnosis, staging, and preoperative planning. Surgical resection, with the goal of R0 resection, remains the cornerstone of treatment, albeit this can be challenging due to tumor location. First-line treatment for advanced DDL involves anthracycline-based therapy. Eribulin and pazopanib show promise in second-line treatment. Ongoing clinical trials suggest a shift towards multimodal therapy. This case report reports the largest retroperitoneal liposarcoma and underscores the complexity of managing retroperitoneal DDL.